Web-Based Patrol Scheduling System in Tinggarjaya Village RT 03 RW 03 Jatilawang District, Banyumas Regency - Nugroho, Andri Mugi Nugroho; Sigit Sugiyanto; Supriyono (Politeknik Piksi Ganesha Indonesia, 2024)
RT 03/03 Tinggarjaya Village, Jatilawang District is one of the RTs in Tinggarjaya Village, Jatilawang District, Banyumas Regency. On RT 03/03, Ronda is held every night. So far, the system for writing patrol schedules and recapping Jimpitan data still uses manual or written by hand and does not use automatic computer storage. No website is still used to record resident data, Jimpitan data, and patrol schedules. This causes less efficiency in making data reports in these activities. This practical work aims to create a simple website that can make creating reports on citizen data, Jimpitan data, and patrol schedules easier. The Patrol Scheduling System was created using the Waterfall model. The application is a tool for creating citizen data reports, traffic jam data, and patrol schedules.